Development of high yielding morphologically improved strains of Pleurotus through interspecific hybridization - JASWAL, RAVINDER K; SODHI, HARPREET S; KAPOOR, S; KHANNA, PRADEEP K (The Indian Journal of Agricultural Sciences, 2026)
The aim of hybridization is to combine desirable characters from different strains and create variability in the existing germplasm. Understanding of heterothallic nature of Pleurotus species makes the breeding programme a success. Pleurotus florida PAU-5 and P. sajor caju PAU-3 were cultivated to raise four and six spore prints which were germinated to isolate 28 and 56 monospores, respectively. Interspecific crosses (1568 no.) were conducted to develop 102 hybrid dikaryons which were shortlisted to 57 hybrids on the basis of endoglucanase activity and subjected to fruiting test. Thirty five hybrids were able to fruit. Maximum harvest of fruit bodies was observed in hybrid no. 42 with 97% biological efficiency (BE). Four hybrid cultures showed higher BE compared to P. florida PAU-5 while seven hybrids gave more yield than P. sajor caju PAU-3. Average weight of a fruit body ranged between 3.3g to 12.5g. Seven hybrids showed morphologically distinct characters. Based on yield and desirable characters, five hybrids were identified. Hybrid no. 8 and 37 showed morphology different from the parent strains while hybrid no. 16 and 46 were similar to the parent P. sajor caju PAU-3 but with higher whiteness index. Hybrid no. 42 was morphologically similar to P. florida PAU-5 but had a 51% higher BE. The strains developed with altered phenotypic expression, viz. pileus shape, colour etc. and better yield indicated usefulness of interspecific hybridization to improve yield and quality. This technique can be extended to improve other characters of Pleurotus namely sporeless strain, strains better suited to changing climate conditions, etc.